Prevention of nasal injury in preterm infants during positive pressure ventilation: a systematic review of interface and dressing selection - Tian Gong; Jia Li Yu; Hua Yang; Yu fan Tang; Ao Huang; Yuan xia Wang (BMC Pediatrics)
Abstract Objective To conduct a systematic review and meta-analysis comparing the incidence of nasal injury in preterm infants undergoing continuous positive airway pressure (CPAP) therapy using nasal masks versus nasal prongs, and to explore the potential effects of prophylactic use of hydrocolloid dressings in reducing nasal injury in preterm infants. Methods On March 1, 2025, we searched the Web of Science, PubMed, Cochrane, and Embase databases for measures and strategies to prevent nasal injury in preterm infants undergoing positive pressure ventilation, and collected relevant randomized controlled trials. The Cochrane Risk of Bias Assessment Tool was used to evaluate the risk of bias in the literature, and the modified Jadad score was used to assess the quality of the studies. Key information was extracted, including the characteristics of the study subjects, interventions, incidence and severity of nasal injury, and failure rate of positive pressure ventilation. Results A total of 12 studies met the inclusion and exclusion criteria, including 1 low-quality study and 11 high-quality studies, with a total sample size of 1,271 participants. Eight studies compared the effects of nasal prongs and nasal masks, with 3 studies investigating the effects of alternating use of nasal prongs and masks. Four studies used hydrocolloid dressings. The results of the meta-analysis showed that the overall incidence of nasal injury was 0.62 (95% CI 0.45–0.87, P = 0.006) in the nasal mask group, 0.95 (95% CI 0.27–3.29, P = 0.093) in the alternating use group, and 0.40 (95% CI 0.30–0.53, P < 0.0001) in the hydrocolloid dressing group. Conclusion The incidence of nasal injury was lower in the nasal mask group compared to the nasal prong group. However, the effect of alternating use of nasal masks and prongs on reducing the incidence of nasal injury was not significant. Prophylactic use of hydrocolloid dressings had a significant effect on reducing the incidence of nasal injury in preterm infants. However, the limited number of existing studies and the small sample sizes of the included studies restricted the generalizability of the conclusions. Future research should further optimize the standardization of interventions and conduct multicenter, large-sample randomized controlled trials to promote continuous improvement in clinical nursing practice.